Efeito de substratos e do sombreamento no desenvolvimento de plantas de palmeira-juçara Euterpe edulis (Mart.) e palmeira-real Roystonea regia (Kunth) - Brahm, Rafael ücker (2010)
The growth of the species of juçara palm Tree Euterpe edulis (Mart.) and royal palm Roystonea regia (Kunth) has no record of studies focusing on south region of Rio Grande do Sul State. It is necessary to identify a system that ensures the proper growth of plants of these species. In this context, these works provide alternatives for producing seedlings with adaptability for family farms of southern half of Rio Grande do Sul. The effect of different substrates on initial growth of the seedlings and the appropriate level of shading for their initial development were determined. The seedlings were grown on Estação Experimental Cascata, Embrapa Clima Temperado. The experiments reported in Chapters I determine the effect of different substrates. The seedlings grew from seeds originated in a family farm located in the municipalities of Tabai and Pelotas, RS. A combination of different substrates was used, represented by the treatments T1 - Plantmax®, T2 - forest soil, T3 - clayey soil, T4 - forest soil:clayey soil 1:1 (v:v), T5 - forest soil:carbonized rice husk 3:1 (v:v), T6 - forest soil:carbonized rice husk 1:1 (v:v), T7 - forest soil:rice husk in natura 1:1 (v:v), T8 - clayey soil:carbonized rice husk 3:1 (v:v), T9 - clayey soil:carbonized rice husk 1:1 (v:v), T10 - clayey soil:rice husk in natura 1:1 (v:v). The experimental design consisted of randomized blocks and the study used a (1 specie x 10 substrates) factorial scheme. Four replicates were used in each experimental design with four seedlings. The seedlings were transplanted into 2 dm³ plastic bags in greenhouse conditions, from January to September, 2009. The experiments were assessed fortnightly considering plants length, stem diameter, number of leaves, number of leaflets, leaflets length, roots length, physical properties of the substrates, macronutrients content of the substrates, and percentage of plants survival at the end of last evaluation. The experiments reported in Chapters II used plants grown from seeds of a family farm located in the municipality of Pelotas, RS. The effect of luminous intensity on palm trees growing in the field was assessed in the experiments. The palm trees were planted in different shading levels: S1 - 0%, S2 - 16%, S3 - 42% and S4 - 73%. 10 The shading was obtained with shade screen for each level of reduced incident radiant, it was placed over each plot represented by a structure of wooden beams with 2.10 m long, 0.70 m tall and 0.50 m wide. The experimental design was randomized blocks consisting of four replications. Each sampling unit was represented by three plants of each species, using 0.30 m row spacing, in the field during nine months. These experiments evaluated fortnightly plants length, stem diameter, number of leaves, number of leaflets, leaflets length, solar radiant incident on the plants, chlorophyll content of plants, roots length, soil physical properties, macronutrients content of soil, and percentage of survival at the end of last evaluation. Data were analyzed using the program statistical program WinSat.